THE INFLUENCE OF AFFILIATE MARKETING AND INFLUENCER MARKETING ON PURCHASE DECISIONS AND DIGITAL MARKETING ACCOUNTABILITY IN E-COMMERCE (STUDY ON STUDENTS OF PGRI UNIVERSITY OF JOMBANG) - Shanti Nugroho Sulistyowati; Niwang Anggarda Gali Paramita (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to examine the utilization of affiliate marketing and influencer marketing in relation to purchasing decisions and digital marketing accountability in e-commerce, with a focus on students at PGRI Jombang University. From an accounting perspective, affiliate marketing and influencer marketing can be viewed as marketing investments whose effectiveness needs to be evaluated through performance measurement and accountability mechanisms. The quantitative approach by applying multiple linear regression analysis in this study. A total of 292 students were selected as samples through a standard random sampling technique was employed for data acquisition through distribution closed questionnaires, which were then processed using SPSS version 16 data processing software. following the outcomes of the examination, it was found that both affiliate marketing and influencer marketing exert a notable effect on consumer purchasing decisions on e-commerce platforms. This indicates that the incorporation of digital marketing approaches through affiliates and influencers is an effective step in influencing consumer buying behavior among young people. The findings indicate that affiliate marketing and influencer marketing contribute positively to purchasing decisions, suggesting that expenditures on digital marketing activities can generate measurable economic benefits and support marketing performance accountability. The results not only demonstrate the effectiveness of affiliate marketing and influencer marketing in influencing purchasing decisions but also provide evidence for evaluating the accountability of digital marketing expenditures and marketing performance measurement in e-commerce businesses.